VARIASI KESOPANAN BERBAHASA PENUTUR BAHASA JAWA - Pradnya Paramita Dewi; Sri Wahyuni (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
Abstract. This study investigates linguistic politeness practiced by the Javanese when they speak Indonesian. To explore variations of such politeness, we probed two major variables: conversational participants and utterance forms. The former includes the aspects of age, social status, and familiarity; whereas the latter covers intonation and word choice. For both variables, we implemented categories of ‘low-high’, ‘equal’, and ‘high-low’. The findings of the study show that, according to the Javanese, instructing a person using the word ‘Ambilkan!’ is polite only when the relational context is ‘high-low’ or ‘equal’; but impolite when the context is ‘low-high’. Based on the utterance form, however, such instruction becomes polite even in the context of ‘low-high’ if the word ‘tolong’ is used.